Peran Lembaga Arbitrase Dalam Penyelesaian Sengketa Bisnis Internasional: Tinjauan Dari Perspektif Teori Sistem Hukum - Kikin Nopiandri (Jurnal Legal Reasoning, 2018)
Business activity becomes more complex whether its subjects, objects, or its model of transactions. That complexity then could cause the dispute between subjects in such business activity, furthermore when the subjects come from different law system background. Such condition need to be responded, and arbitration could become one of the suit mechanism to settle the dispute in business activity relationship. In Indonesia, regarding to arbitration mechanism, the Indonesian National Arbitration Board (BANI) had already been established under the Act Number 30 Year 1999 on Arbitration and Alternative Dispute Resolution. This study focuses on how arbitration institution plays its role in international transaction dispute settlement. This study uses normative legal research method, and based on secondary data. As a legal structure, arbitration, when it plays its role as a body of mechanism in dispute settlement, it could give advantage to make dispute settlement easier or simpler rather than process of law through court mechanism. That is because the arbitration, such as BANI, implements the simple organizational structure principle, in which an organization has to become lean structure relatively, but still has many functions. Furthermore, both of arbitration institution and business entity have similarity in culture regarding to the spirit of work. When doing something, both of them tend to do it efficiently and effectively wheather from time or cost aspect.